PERBANDINGAN METODE EKSTRAKSI EKSTRAK UMBI BAWANG RAMBUT (Allium chinense G.Don.) MENGGUNAKAN PELARUT ETANOL 70% TERHADAP RENDEMEN DAN SKRINING FITOKIMIA - Supomo, Supomo; Warnida, Husnul; Said, Bagus Moch (APDFI (Asosiasi Pendidikan Diploma Farmasi Indonesia), 2019)
Allium chinense are plants that contain bioactive compounds such as alkaloids, flavonoids, and saponins. The rendement of an extract may be affected by the extraction mentod used. This study aims to determine the effect of maseration and digestion extraction method on rendemen and identification of secondary metabolite in the extract of the hair onion bulbs. Research conducted is an experimental study. The samples used were hair bulbs obtained in Kota Bangun, East Kalimantan, extracted wiyh 2 extraction methods of maceration and digestion using ethanol 70% solvent and done as much as 3 times replication. Identification of secondary metabolite compounds was performed by phytochemical screening including test of alkaloids, flavonoids, saponins, tannins, and steroids. From the test data is processed by statistical analysis. The result of rendement with 3 times replikation of digesti mentod obtained by 20,02 gram, 19,03 gram, and 19,17 gram. While the maseration method obtained for 12,38 grams, 12,45 grams, and 15,91 grams. So there are differences between the results of the results of digestion mentod and maseration mentod. Based on phytochemical screening tets showed that the thick extract of hair onion bulbs contain compounds alkaloids, flavonoids, and saponins.